Identification and chromosomal location of genes resistance to leaf rust in lines of common wheat (Experimental biology, 2015)
Resistance of short stature sample line SIM79/279 and k-24/20989 inherited by the type of epistasis and complementary interaction of genes. Genes resistance to leaf rust SIM79/279 allelic to highly effective tester genes, Lr10, Lr26, Lr28, Lr29, Lr34, Lr39, Lr50 and line k-24/20989 - Lr1, Lr9, Lr10, Lr28, Lr29, Lr39, Lr50 of variety Thatcher. Main genes high resistance to leaf rust of lines SIM79/279 and k-24/20989 have localized in chromosome 1B, 1A and 6B, 5D, respectively.
Keywords: wheat; leaf rust; tester; allele; gen; localization; identification